2015
DOI: 10.1109/jetcas.2015.2433552
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Spiking Neuromorphic System for Real-World Pattern Recognition

Abstract: Abstract-A neuromorphic chip that combines CMOS analog spiking neurons and memristive synapses offers a promising solution to brain-inspired computing, as it can provide massive neural network parallelism and density. Previous hybrid analog CMOS-memristor approaches required extensive CMOS circuitry for training, and thus eliminated most of the density advantages gained by the adoption of memristor synapses. Further, they used different waveforms for pre and post-synaptic spikes that added undesirable circuit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 73 publications
1
73
0
Order By: Relevance
“…Consequently, it is natural to envision a verylarge-scale integrated (VLSI) Neuromorphic SoC built using CMOS neurons and RRAM synapses. Few research groups, including ours, have developed prototype chips and demonstrated such neural motifs with small-scale spiking neural networks [10], [11], [45]. In these works, analog-like conductance modulation capability that supports continuous weight change is required for effective STDP learning [2], [10].…”
Section: Stdp Learning and Emerging Nvm Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is natural to envision a verylarge-scale integrated (VLSI) Neuromorphic SoC built using CMOS neurons and RRAM synapses. Few research groups, including ours, have developed prototype chips and demonstrated such neural motifs with small-scale spiking neural networks [10], [11], [45]. In these works, analog-like conductance modulation capability that supports continuous weight change is required for effective STDP learning [2], [10].…”
Section: Stdp Learning and Emerging Nvm Devicesmentioning
confidence: 99%
“…Further, these devices have shown low-energy consumption to change their states and very compact layout footprint [4]- [9]. Hybrid CMOS-RRAM analog very-largescale integrated (VLSI) circuits have been proposed [10], [11] [20,21] to achieve dense integration of CMOS neurons and emerging devices for neuromorphic system-on-a-chip (NeuSoC). Fig.1a illustrates a NeuSoC architecture where a three layer fully-connected spiking neural network is envisioned.…”
Section: Introductionmentioning
confidence: 99%
“…The memristive synapse, for the given sizing for M 1 , realizes LRS and HRS resistances of 0.4M Ω and 16M Ω respectively, providing significant improvement over contemporary memristive devices. As detailed in [22], [30], the traditional subthreshold neuron designs are not suitable for driving memristive load. The opamp-based integrate-andfire neurons with winner-take-all STDP learning interface from author's prior work in [30] can directly be adapted to interface with the presented synapses; higher LRS resistance will further help simply opamp design.…”
Section: Memristive Synapse Circuitmentioning
confidence: 99%
“…11A. This three neurons and two synapses system is widely used for describing and analyzing the behaviour of neural circuits [39], [64], [65]. Moreover, the low complexity of the system allows to perform an electrical simulation.…”
Section: Synapse and Stdpmentioning
confidence: 99%
“…many studies have been made to exploit memristors with the purpose of realizing plastic synapses within neuromorphic systems [29,32,33,34,35,36,37,38,39].…”
mentioning
confidence: 99%